Classification of monuments in Czech legislation - Dąbkowska, Monika (Protection of Cultural Heritage, 2016)
In Czechia, provisions of law pertaining to historic preservation were established in 1958, during Stalinism. The regulations were provided in Czechoslovakian Act on Cultural Monuments. It was superseded by the Act on State Care for Historic Monuments and Sites being currently in force, which was adopted in the former political system in 1987. Due to dynamic economic, political, and ownership-related transformations taking place at that time, it was necessary to amend it. Consequently, for several years, the legislators have been working on a new act referred to as “The Act on Protection of Resources of Historic Monuments and Sites.” This article pertains to legislative solutions and classification of historic monuments and sites in the light of the Act being developed. In this document, historic monuments and sites are not grouped into specific categories. Instead, they are all considered material elements of cultural heritage. On the other hand, assets of historical significance are classified into cultural monuments, monument ensembles, and national culture monuments and sites of the most outstanding significance. Additionally, two temporary forms of historic preservation have been developed: areas and reserves of historical significance. Archaeological monuments and properties considered as having outstanding historical values under certain international agreements are treated separately. This classification allows for assigning tasks to appropriate administrative bodies and, at the same time, encouraging institutions responsible for historic preservation of monuments and sites on the national level to become advisory bodies of regional administration institutions. What is worth mentioning in the field of historic preservation in Czechia are government’s attempts at making historic monuments and sites more available to citizens by introducing certain legal regulations, i.e. providing the government with pre-emptive right to purchase a property of historical significance from a private owner. This approach results in increasing government’s profits from tourism and culture-related products.